Understanding Values Work Institutional Perspectives in Organizations and Leadership - Askeland, Harald; Espedal, Gry; Jelstad Løvaas, Beate; Sirris, Stephen (Springer Nature, 2020)
At the core of institutional theories, 'values' is a central term and figures in most definitions; however it remains understudied and under-explored. The editors of this open access book identify a resurgence of interest in the values-construct which underpins discussions of identity, 'ethos' and the purpose/nature of public and civic welfare provision. Considering the importance of values and values work to social, material and symbolic work in organizations, individual chapters explore values work as performed in organizations and by leaders. Focusing on practices of values work, the book applies and combines different theoretical lenses exemplified by the integration of institutional perspectives with micro-level perspectives and approaches.